2015
DOI: 10.1044/2015_lshss-14-0020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coaching on Educators' and Preschoolers' Use of References to Print and Phonological Awareness During a Small-Group Craft/Writing Activity

Abstract: Professional development that included coaching with a speech-language pathologist enabled educators and children to engage in more phonological awareness talk during this activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
1
16
0
1
Order By: Relevance
“…Although the results of the present study are promising, additional studies with larger sample sizes are needed to confirm the effectiveness of coaching-in particular, its impact on children. However, the findings of the present study, in addition to parallel studies that have focused on vocabulary and code-related talk (Milburn et al, 2015;Namasivayam et al, 2015), provide relevant information on the domains that may be most sensitive to change with this teaching approach. In fact, these studies suggest that the added value of five individual coaching sessions on educators' behaviors consists of fine tuning specific strategies (i.e., vocabulary and phonological awareness teaching, elicitation of experiential reasoning).…”
Section: The Role Of Coaching In Professional Development Programsmentioning
confidence: 71%
See 3 more Smart Citations
“…Although the results of the present study are promising, additional studies with larger sample sizes are needed to confirm the effectiveness of coaching-in particular, its impact on children. However, the findings of the present study, in addition to parallel studies that have focused on vocabulary and code-related talk (Milburn et al, 2015;Namasivayam et al, 2015), provide relevant information on the domains that may be most sensitive to change with this teaching approach. In fact, these studies suggest that the added value of five individual coaching sessions on educators' behaviors consists of fine tuning specific strategies (i.e., vocabulary and phonological awareness teaching, elicitation of experiential reasoning).…”
Section: The Role Of Coaching In Professional Development Programsmentioning
confidence: 71%
“…Namasivayam et al (2015) showed that the children in the workshop plus coaching group engaged in more vocabulary-related talk during a shared book reading activity relative to children in the comparison group, whose educators received only workshops. In a second study, Milburn et al (2015) observed that workshops plus coaching significantly affected the number of educators' and children's utterances related to phonological awareness-a skill that has not shown improvements in previous studies (Landry, Swank, Smith, Assel, & Gunnewig, 2006;Neuman & Wright, 2010). Further studies focusing on different areas of language and literacy-in particular on conversations and decontextualized language-are needed to explore the specific effect of coaching on interactive shared reading.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Along with these elements, 11 studies included a workshop; these were held at the beginning of the intervention or at intervals across the duration of the PDL interventions (e.g. Powell et al ., ; Lonigan et al ., ; Milburn et al ., ). This combination of approaches appears to be effective.…”
Section: Resultsmentioning
confidence: 97%